2020
DOI: 10.1002/jmv.25665
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of immune status against measles, mumps, and rubella in young Kuwaitis: MMR vaccine efficacy

Abstract: Seroprevalence studies on measles, mumps, and rubella immunoglobulin G (IgG) antibodies after the implementation of the measles‐mumps‐rubella (MMR) vaccine are lacking in Kuwait. This study is an age‐stratified serological study to assess the herd immunity to measles, mumps, and rubella among the young Kuwaiti population to evaluate the effectiveness of the MMR vaccine. IgG antibody titers to mumps, measles, and rubella were determined with commercial immune‐assay in serum samples of 1000 Kuwaitis aged 5 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Consistent with reports by other researchers, our data showed no significant change in the mumps seropositivity rate among men and women. 38,43,44 Similar to several previous studies; however, a higher mumps seronegativity rate was reported among men than among women. 20,38 Interestingly, we showed in a previous study, a significant association between age as well as measles seropositivity.…”
Section: Effects Of Age Group and Gender On Mumps Serostatussupporting
confidence: 88%
See 3 more Smart Citations
“…Consistent with reports by other researchers, our data showed no significant change in the mumps seropositivity rate among men and women. 38,43,44 Similar to several previous studies; however, a higher mumps seronegativity rate was reported among men than among women. 20,38 Interestingly, we showed in a previous study, a significant association between age as well as measles seropositivity.…”
Section: Effects Of Age Group and Gender On Mumps Serostatussupporting
confidence: 88%
“…38,43,44 Similar to several previous studies; however, a higher mumps seronegativity rate was reported among men than among women. 20,38 Interestingly, we showed in a previous study, a significant association between age as well as measles seropositivity. 45 Our results showed that the median anti-mumps IgG concentration was higher in women than in men for all age groups.…”
Section: Effects Of Age Group and Gender On Mumps Serostatussupporting
confidence: 88%
See 2 more Smart Citations
“…Up to now, only one genetically stable serotype of rubella virus has been identified 16 . Rubella is a vaccine‐preventable and self‐limiting disease that usually occurs during childhood 17 . Besides vaccination, natural infection with the rubella virus can also lead to long immunity 18 .…”
Section: Introductionmentioning
confidence: 99%